Analysis of integration method in multi-heat-source power generation systems based on finite-time thermodynamics. (15th September 2020) - Liu, Hongtao; Zhai, Rongrong; Patchigolla, Kumar; Turner, Peter; Yang, Yongping
Highlights: A general integration method of multi-heat-source systems is proposed. The external and internal irreversibility due to finite-time was considered. The distribution diagram of the optimum thermodynamic structure was drawn. Four coupled systems were applied to determine the optimum integration position. Abstract: Multi-heat-source power generation system is a promising technology to reduce fossil fuel consumption and save investment costs by integrating several heat sources and sharing power equipment components. Researchers have conducted many case studies based on specific power plants to find the preferred integration scheme. However, there is still no unified theory to guide the integration of different energy sources. To explore a common method to integrate various energy sources, this work developed a general multi-heat-source integrated system model based on finite-time thermodynamics, considering the external and internal irreversibility due to the constraint of finite-time and finite-size. The generalised expressions for optimum integration method are explored and expressed in dimensionless parameters. This study indicated the system with two heat-sources performs differently in four regions due to the variation of endothermic temperatures. The characteristics of energy flow and irreversibility reveal that by adding a second heat-source, the first heat-source energy can be substantially reduced at the cost of system efficiency slightly decreasing. Then four application cases for solar-aided coal-fired power plants are conducted to check its feasibility and potential to provide the performance bound of integrating multi-heat-sources.